2019
DOI: 10.1007/s12325-019-01012-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient Preferences for Treatment Decisions for New Direct Acting Antiviral (DAA) Therapies for Chronic Hepatitis C Virus Infections

Abstract: IntroductionThe new direct acting antiviral (DAA) therapies are able to effectively treat chronic hepatitis C (CHC). This study elicited the preferences of CHC patients for treatment attributes of new DAAs.MethodsAn online discrete choice experiment survey was designed to collect data from adult CHC patients in the USA, UK, France, Germany, Spain, and Italy. Patients were asked to choose from alternative hypothetical DAA options, defined by differing levels of nine attributes [i.e., treatment duration, tablet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 26 publications
2
20
0
5
Order By: Relevance
“…Although similar high SVR12 rates are observed for the 12-week G/P regimen, patients may prefer a shorter duration because it is more convenient and requires less monitoring [9]. requested by any qualified researchers who engage in rigorous, independent scientific research, and will be provided following review and approval of a research proposal and Statistical Analysis Plan (SAP) and execution of a Data Sharing Agreement (DSA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although similar high SVR12 rates are observed for the 12-week G/P regimen, patients may prefer a shorter duration because it is more convenient and requires less monitoring [9]. requested by any qualified researchers who engage in rigorous, independent scientific research, and will be provided following review and approval of a research proposal and Statistical Analysis Plan (SAP) and execution of a Data Sharing Agreement (DSA).…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, TN patients without cirrhosis and with CC represent 98% of the HCV patient population [ 16 ]; therefore, the majority of patients are eligible for 8-week treatment. Although similar high SVR12 rates are observed for the 12-week G/P regimen, patients may prefer a shorter duration because it is more convenient and requires less monitoring [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization has established targets for HCV elimination by 2030; however, current rates of HCV treatment have been declining in the US, which can be Given the similar high cure rates and safety profiles of contemporary HCV regimens, HCV patients' preferences for therapy may be influenced by treatment attributes other than cure rates and tolerability. Treatments that are more convenient and require less disruption to their daily life (e.g., shorter treatment duration, no modification in PPI use, and fewer office visits when on treatment) are important to patients with HCV and should be considered when making treatment decisions [15].…”
Section: G/p Was Recently Approved By the Us Food Andmentioning
confidence: 99%
“…In addition, only one study has focused on the level of engagement of individuals with HCV in their treatment regimen or levels of patient activation. Welzel et al (2019) found that approximately 20% of HCV patients studied may lack the basic knowledge and confidence to be an active participant in their health care. Because the antiviral medication treatment is complex, including laboratory blood draws and clinic visits, patient adherence is critical to achieving a sustained virologic response.…”
mentioning
confidence: 99%